CHILD COACHES AND THE EARLY CONSTRUCTION OF THE IDEAL OF SUCCESS: IMPACTS ON SCHOOL RETENTION OF CHILDREN AND ADOLESCENTS - Justi, Jadson; Ramos, Ana Cristina Figueira de Almeida de Souza (Seven Editora, 2026)
The phenomenon of child coaches represents a contemporary manifestation of the culture of entrepreneurship that reaches children and adolescents, promoting discourses on early success and productivity. Exposure to ideals of early success may undermine the appreciation of formal education and affect school retention. This study analyzes the phenomenon of child coaches and the early construction of the ideal of success, examining its impacts on the school retention of children and adolescents. The methodology is characterized as an exploratory bibliographic review with a qualitative approach, grounded in the critical analysis of scientific publications from 2020 to 2025. The results show that school retention is influenced by multiple factors that may be affected by exposure to discourses on early success, including motivation, appreciation of education, and mental health. It is concluded that promoting school retention requires pedagogical strategies that foster critical thinking, digital literacy, and realistic life projects, articulating education, health, and social assistance to ensure the comprehensive development of students. DOI: https://doi.org/10.56238/sevened2026.008-089